2019
DOI: 10.2174/1389450120666190708100308
|View full text |Cite
|
Sign up to set email alerts
|

Circulating and Tissue microRNAs as Biomarkers for Ovarian Cancer Prognosis

Abstract: Ovarian cancer (OC) is one of the most common cancers globally with a high rate of cancer- associated mortality. OC may be classified into epithelial cell neoplasms, germ cell neoplasms and stromal cell neoplasms. The five-year survival in the early and advanced stages of disease is approximately 90% and 15%, respectively. microRNAs are short, single-stranded, non-coding ribonucleic acid (RNA). miRNAs play critical roles in post transcriptionally regulations of gene expression. miRNAs are found in different ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…MicroRNAs (miRNAs) have recently demonstrated promise in the diagnosis of other types of cancer ( Poel et al, 2018 , Montazerian et al, 2018 , Otandault et al, 2019 ) owing to their stability and relative ease of detection in blood samples, allowing minimally invasive, repeated sampling. Importantly miRNAs are aberrantly expressed in a number of cancers ( Pendlebury et al, 2017 , Deb et al, 2018 , Parizadeh et al, 2019 ), including HGSC ( Liu et al, 2019 ), where they have been shown to accelerate tumor migration and invasion ( Liu et al, 2019 ). However reduced expression of miRNAs can have the opposite effect, miR182 was associated with higher expression of discoidin domain receptor 2 (DDR2), a tumour promoter, in women with HGSC ( Ramalho et al, 2019 ) and lower circulating levels of miR182 had a worse prognosis ( Ramalho et al, 2019 ) suggesting that miRNAs both positively and negatively regulate tumour growth and disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) have recently demonstrated promise in the diagnosis of other types of cancer ( Poel et al, 2018 , Montazerian et al, 2018 , Otandault et al, 2019 ) owing to their stability and relative ease of detection in blood samples, allowing minimally invasive, repeated sampling. Importantly miRNAs are aberrantly expressed in a number of cancers ( Pendlebury et al, 2017 , Deb et al, 2018 , Parizadeh et al, 2019 ), including HGSC ( Liu et al, 2019 ), where they have been shown to accelerate tumor migration and invasion ( Liu et al, 2019 ). However reduced expression of miRNAs can have the opposite effect, miR182 was associated with higher expression of discoidin domain receptor 2 (DDR2), a tumour promoter, in women with HGSC ( Ramalho et al, 2019 ) and lower circulating levels of miR182 had a worse prognosis ( Ramalho et al, 2019 ) suggesting that miRNAs both positively and negatively regulate tumour growth and disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are short non-coding RNA sequences from 17 to 25 nucleotides in length, regulating gene expression at the post-transcriptional level [ 73 ]. Aberrant expression of various specific miRNAs has been observed in various tumors, including breast [ 74 , 75 ], lung [ 76 ], colorectal cancer [ 77 ], ovarian [ 78 ], and prostate cancer [ 79 ]. This feature allows not only to distinguish tumor tissue from normal tissue but also to classify tumors according to the tissue origin, and to perform tumor staging [ 80 ], which potentially makes miRNAs a biomarker efficient for prognosing the development of oncological diseases [ 81 ].…”
Section: Exosomal Mirnasmentioning
confidence: 99%
“…Therefore, effective methods for early diagnosis and grading hepatic fibrosis must be developed. Circulating and exosomal miRNAs could be used as markers for diagnosis or indicators for determining severity of certain diseases and therapeutic effects [9799]. For example, elevated miR-21, miR-122 and miR-223 in the serum may serve as new biomarkers for liver injury diseases such as liver cancer and chronic hepatitis [100].…”
Section: Using Mirnas To Grade Schistosomiasis-associated Hepatic Fibmentioning
confidence: 99%